Proceedings of the International Conference on Emerging Media, and Social Science 2019
DOI: 10.4108/eai.7-12-2018.2281768
|View full text |Cite
|
Sign up to set email alerts
|

EFL Learning Media: Perspective on E-Learning through Google Classroom

Abstract: Welcoming the fast development of technology, educators nowadays have a lot of variation in giving knowledge and practices. Intensive meetings inside the classroom need to be explored more following their habit in using gadgets for daily life activities. To get meaningful access with individual student, Google facilitates new media for teachers to conduct E-learning through Google Classroom (GC) application. This study aims to investigate how the educators and learners respond their online course activities. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…In 2018, Al-Maroof and Al-Emran (2018) adopting Technology Acceptance Model (TAM), reported that the two features (usefulness and ease) affect significantly the chosen sample of undergraduates' intention as GC works as a facilitator to develop their learning activities. As a result, GC can be a potential tool for teaching and learning (Iftakhar, 2016) and receives positive satisfaction in the area of access, communication and interaction (Shaharanee et al, 2016) providing that both teachers and students understand how to use it (Megawati & Astutik, 2018).…”
Section: Video Conference Learning Management System and Applicatiomentioning
confidence: 99%
“…In 2018, Al-Maroof and Al-Emran (2018) adopting Technology Acceptance Model (TAM), reported that the two features (usefulness and ease) affect significantly the chosen sample of undergraduates' intention as GC works as a facilitator to develop their learning activities. As a result, GC can be a potential tool for teaching and learning (Iftakhar, 2016) and receives positive satisfaction in the area of access, communication and interaction (Shaharanee et al, 2016) providing that both teachers and students understand how to use it (Megawati & Astutik, 2018).…”
Section: Video Conference Learning Management System and Applicatiomentioning
confidence: 99%
“…It can make students excited and inspired to develop their English learning achievement. As a result, social media can be an expected apparatus for educating and learning (Iftakhar, 2016) also, gets positive fulfillment in the space of access, correspondence and communication (Shaharanee et al, 2016), giving those teachers and student see how to utilize it (Megawati & Astutik, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Because of the variety of media, it has different characteristics. (Megawati & Astutik, 2019)Media are tools that the teacher uses in the teaching-learning process. The uses of media help the students master the material presented by the teachers more easily.…”
Section: Page505 Of 514mentioning
confidence: 99%